Monetary policy and wealth inequality in South Africa: Evidence from tax administrative data - Goodness C. Aye; Laurence Harris; Junior T. Chiweza (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
This paper examines the relationship between monetary policy and wealth inequality in South Africa. We employed a unique database of tax administrative data which allowed us to account for individual heterogeneity. These tax data span from 2011 to 2017 and include over 3 million individual taxpayers in South Africa after data cleaning. Results based on fixed- and random-effects panel model estimates show that monetary policy generally increases wealth Gini inequality while it decreases the wealth 90-10 percentile differential. Increasing asset prices and gross domestic product per capita generally increases wealth inequality, while inflation reduces wealth inequality. The effect of age on wealth distribution varies depending on whether a fixed- or random-effects panel model is considered. Based on the estimates and observed data, being male tends to increase wealth inequality.
Keywords: C23; D14; D31; E52; 330; monetary policy; wealth inequality; distribution; tax data; heterogeneity